A social-ecological systems approach for environmental management. (1st August 2016) - Virapongse, Arika; Brooks, Samantha; Metcalf, Elizabeth Covelli; Zedalis, Morgan; Gosz, Jim; Kliskey, Andrew; Alessa, Lilian
Abstract: Urgent environmental issues are testing the limits of current management approaches and pushing demand for innovative approaches that integrate across traditional disciplinary boundaries. Practitioners, scholars, and policy-makers alike call for increased integration of natural and social sciences to develop new approaches that address the range of ecological and societal impacts of modern environmental issues. From a theoretical perspective, social-ecological systems (SES) science offers a compelling approach for improved environmental management through the application of transdisciplinary and resilience concepts. A framework for translating SES theory into practice, however, is lacking. In this paper, we define the key components of an SES-based environmental management approach. We offer recommendations for integrating an SES approach into existing environmental management practices. Results presented are useful for management professionals that seek to employ an SES environmental management approach and scholars aiming to advance the theoretical foundations of SES science for practical application. Highlights: Novel management approaches are needed to address current environmental challenges. Social-ecological systems science offers new approaches for environmental management. A framework to translate social-ecological systems theory into practice is lacking. We propose a social-ecological systems (SES) environmental management framework. The SES framework is useful for management professionals and scholars of SES science.